The Art of Traditional Singing in Namangan Region and the Role of Kamoliddin Rakhimov in It - Rustamov Shakhzodbek Shukhratjon ugli; Yusupov Oybek Ulugbek ugli (Genius Journals, 2023)
This article provides detailed information about the reforms in the field of culture and art in the Republic of Uzbekistan, the analysis of the life, creative activity and works of the people’s artist of Uzbekistan Kamoliddin Rakhimov, one of the representatives of the traditional singing art of Namangan region
Keywords: music; creator; art; work